Innervation of the pineal gland in the rat: A chromotolysis study - Ali, Hadi J. (AL-Kindy College Medical Journal, 2011)
Back ground: The innervations of the pineal gland from the superior cervical ganglion have shown some form of a chromatolysis reaction. Objective: 1-Tracing the innervations of the pineal gland by removing the target tissue (the pineal gland in this study) i.e. (pinealoctomy) and removal of the superior cervical ganglion i.e. (ganglionectomy). 2- The localization and total number of the neurons which project into the rat pineal gland 3-The effect of pinealoctomy on the SCG after a different time interval. Methods: Twenty five albino rats were used in this study, Pinealoctomy was done, then after a different time interval ganglionectomy was done, in order to study the Chromatolysis in their cell body. Result: The present study has demonstrated that the chromatolysis reaction in the neurons following Pinealoctomy confirms the innervations of the pineal gland from the SCG. The present study has demonstrated that the most obvious the Chromatolysis reaction occurred one day after pinealoctomy. Conclusion: This study confirms the innervations of the pineal gland from the SCG, the study shows that the distribution of the Chromatolysis neurons; of all age group occurred in all parts of the ganglion; although it was more abundant in the rostal 2/3.